2016
DOI: 10.5209/rev_infe.2016.v7.n1.52130
|View full text |Cite
|
Sign up to set email alerts
|

Migrant domestic workers, vulnerability and the law: immigration and employment laws in Cyprus and Spain

Abstract: The intersection of gender, welfare and immigration regimes has been one of the main focus of a rich scholarship on paid domestic work in Europe. This article brings into the discussion the nexus of employment and immigration law regimes to reflect on the role of legal regulation in structuring and reducing the vulnerability of domestic workers. I analyse this nexus by looking at the cases of Cyprus and Spain, two states falling under the cluster of Southern Mediterranean welfare regimes, that share certain ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…Our findings also reflect recent work reporting on the state of migrant domestic work in Cyprus [8,25]. Employment and immigration visa requirements such as "tied visa" schemes and shared accommodation with employers increase women's vulnerability to sexual violence [26] and their ability to escape from dangerous situations and achieve retribution through controlling women's mobility and associations [4,7]. Legal frameworks [27], in combination with embedded social stereotypes, institutional racism, and discrimination [17,28], made it almost impossible for women to find justice and retribution.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our findings also reflect recent work reporting on the state of migrant domestic work in Cyprus [8,25]. Employment and immigration visa requirements such as "tied visa" schemes and shared accommodation with employers increase women's vulnerability to sexual violence [26] and their ability to escape from dangerous situations and achieve retribution through controlling women's mobility and associations [4,7]. Legal frameworks [27], in combination with embedded social stereotypes, institutional racism, and discrimination [17,28], made it almost impossible for women to find justice and retribution.…”
Section: Discussionsupporting
confidence: 86%
“…The Human Rights Watch, among others, has reported on domestic workers' exploitative working conditions, with excessively long and often unpaid hours of work, restrictions on freedom of movement, and contact with others [4,5] in what Jureidini and Moukarbel aptly describe as "contract slavery" [6]. In the literature, authors have reported on the increased risk for abuse faced by domestic workers (e.g., [7][8][9]), whilst the sexualised nature of domestic work, the heightened power imbalance between employer and employee, and the confinement of work within the private sphere places women at particular risk for workplace sexual harassment and assaults [10][11][12]. A high incidence of sexual harassment is reported among domestic workers, especially those living in their employer's residence [11].…”
Section: Introductionmentioning
confidence: 99%
“…Women PDWs continue to be debarred from basic working provisions such as maximum work time, remuneration for overtime, and security in relation to night work (Albin & Mantouvalou, 2012; Mundlak & Shamir, 2011; Pavlou, 2016). Mundlak and Shamir (2014) discuss the lack of unity among the PDWs to organize themselves collectively in the traditional sense, such as through trade unions, rendering their attempts futile.…”
Section: The Exploitative Nature Of Domestic Workmentioning
confidence: 99%